Electroweak parameters of the Z° resonance and the standard model - Dova, María Teresa (1992)
The four LEP experiments have each performed precision measurements of Z ° parameters. A method is described for combin- ing the results of the four experiments, which takes into account the experimental and theoretical systematic errors and their correlations. We apply this method to the 1989 and 1990 LEP data, corresponding to approximately 650 000 Z ° decays into hadrons and charged leptons, to obtain precision values for the Z ° parameters. We use these results to test the standard model and to constrain its parameters.